Multiscale magnetization in cobalt-doped ferrite nanocubes - Zákutná, Dominika; Fischer, Anne; Dresen, Dominique; Nižňanský, Daniel; Honecker, Dirk; Disch, Sabrina (Journal of applied crystallography, 2022)
The magnetization of cobalt ferrite nanocubes of similar size, but with varying Co/Fe ratio, is extensively characterized on atomistic and nanoscopic length scales. Combination of X-ray diffraction, Mössbauer spectroscopy, magnetization measurements and polarized small-angle neutron scattering (SANS) reveals that a lower amount of cobalt leads to an enhanced magnetization. At the same time, magnetic SANS confirms no or negligible near-surface spin disorder in these highly crystalline, homogeneously magnetized nanoparticles, resulting in an exceptionally hard magnetic material with high coercivity.
Keywords: Mössbauer spectroscopy; magnetic small-angle neutron scattering; coercivity; near-surface spin disorder; nanoparticles; ferrite